1982
DOI: 10.1002/jlac.198219820206
|View full text |Cite
|
Sign up to set email alerts
|

2,2,4‐Trisubstituted 2H‐1,3‐Oxazetes ‐ A New Type of Heterocycles ‐ A Reinvestigation

Abstract: The recently described reaction between lithium hydride and addition products of acyl isothiocyanates with amines, methanol, and methanethiol in DMF followed by alkylation with methyl iodide is shown not to generate a new class of heterocycles -2,2,4-trisubstituted 2H-3,3-oxazetes but to yield N-acyl isothioureas, N-acyl mono-, and -dithioisocarbamates, respectively. The structures are confirmed by IR, mass, 'H-NMR, and 13C-NMR spectra. 2,2,4-Trisubstituierte ZH-l,3-Oxazete -Ein neuer Typ von Heterocyclen -Ein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Several oxazete derivatives have been synthetized using some reagents such as mesitonitrile oxide [41], α,α-bis-(alkylthio) oxime [42], acylisothiocyanate [43] and others. In this study, an azete derivative was prepared via intramolecular reaction by displazament of nitro group in mild conditions (Fig.…”
Section: Preparation Of a Steroid-oxazole-12′-[13] Oxazete] Derivativementioning
confidence: 99%
“…Several oxazete derivatives have been synthetized using some reagents such as mesitonitrile oxide [41], α,α-bis-(alkylthio) oxime [42], acylisothiocyanate [43] and others. In this study, an azete derivative was prepared via intramolecular reaction by displazament of nitro group in mild conditions (Fig.…”
Section: Preparation Of a Steroid-oxazole-12′-[13] Oxazete] Derivativementioning
confidence: 99%
“…It is noteworthy that several epoxides have been prepared using different protocols; nevertheless, expensive reagents and special conditions are required; the most widely practiced methods employ some reagents such as Co(III) [45] and Cr(III) [46]. In this study, three epoxide derivatives (compounds 8, 9 and 10) were prepared by the reaction of 7 with aldehyde derivatives in mild conditions ( Figure 6).…”
Section: Preparation Of Epoxide Derivativesmentioning
confidence: 99%
“…There are several studies which have shown that molecular orbitals and frontier electron density can be used to predict the most reactive position in some electron system on several types of reactions [30,31]. In this way, the values of highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO) and their energy gap reflect the chemical activity of a molecule [32].…”
Section: Electronic Parametersmentioning
confidence: 99%